Rare-earth doped BiFe0.95Mn0.05O3 nanoparticles for potential hyperthermia applications - Dubey, Astita; Salamon, Soma; Attanayake, Supun B.; Ibrahim, Syaidah; Landers, Joachim; Castillo, Marianela Escobar; Wende, Heiko; Srikanth, Hari; Shvartsman, Vladimir V.; Lupascu, Doru C. (Frontiers in Bioengineering and Biotechnology, 2022)
Ionic engineering is exploited to substitute Bi cations in BiFe0.05Mn0.05O3 NPs (BFM) with rare-earth (RE) elements (Nd, Gd, and Dy). The sol-gel synthesized RE-NPs are tested for their magnetic hyperthermia potential. RE-dopants alter the morphology of BFM NPs from elliptical to rectangular to irregular hexagonal for Nd, Gd, and Dy doping, respectively. The RE-BFM NPs are ferroelectric and show larger piezoresponse than the pristine BFO NPs. There is an increase of the maximum magnetization at 300 K of BFM up to 550 % by introducing Gd. In hyperthermia tests, 3 mg/mL dispersion of NPs in water and agar could increase the temperature of the dispersion up to ~39 °C under an applied AC magnetic field of 80 mT. Although Gd doping generates the highest increment in magnetization of BFM NPs, the Dy-BFM NPs show the best hyperthermia results. These findings show that RE-doped BFO NPs are promising for hyperthermia and other biomedical applications.